Effect of transitional nursing care on quality of life among patients with type 2 diabetes: A meta-analysis of randomized controlled trials - Alfiani Rahmi Putri; Saranya Pimolkatekul; Yan Adi Wibawa; Nguyen Ngoc Thanh; Tirza Jo Lawrence; Made Satya Nugraha Gautama (Tehran University of Medical Sciences, 2023)
Background & Aims: Type 2 diabetes accounts for 95% of all diabetes cases worldwide, and its prevalence continues to rise. The constant management of blood glucose levels can be burdensome, further deteriorating patients' quality of life. This study aims to determine the effect of transitional nursing care on the quality of life among adults with type 2 diabetes. Methods & Materials: We conducted a meta-analysis of randomized controlled trials (RCTs) to determine the effectiveness of transitional nursing care on the quality of life of adults with type 2 diabetes. We searched for published Randomized Controlled Trials (RCTs) on PubMed, Embase, CINAHL, and the Cochrane Library. The process of study selection spanned from March 2023 to April 2023. Data synthesis was performed using Review Manager 5.4 to generate pooled effect size estimates. Results: A total of six studies were included in our analysis. Our results showed that transitional care significantly improved the quality of life of adults with type 2 diabetes (SMD= 0.55, 95% CI: 0.15, 0.95, Z= 2.72, p= 0.007). Compared to usual care, transitional care also significantly lowered HbA1c levels (MD= -0.39, 95% CI: -0.70, -0.07, Z= 2.41, p= 0.02). Conclusion: Our research identified that transitional nursing care significantly improved the quality of life among adults with type 2 diabetes. Nurses should take into account our positive findings when implementing this care model for these patients. We suggest that future researchers carry out more studies with a focus on transitional nursing care for patients with type 2 diabetes to investigate its impacts further.